Cultivating Green Behavior of Eco Literation-Based Elementary School Students during the COVID-19 Pandemic - Hana Lestari; Ridwan Siskandar (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to describe how to grow the green behavior of elementary school students based on Eco literation during the COVID-19 pandemic. The method used is a literature review with a systematic mapping study technique as a library search. Based on the results of the study, Green behavior that is grown in children based on Eco literation includes 4 components of Eco literation, namely implications, ecological knowledge, knowledge of environmental problems and environmentally responsible behavior. Through these 4 literacy components children can have a concern for health, personal hygiene and care for the environment, the ability to communicate and apply ecological concepts, an understanding of various problems and issues related to the environment that are influenced by aspects of politics, education, economy, and government institutions and active participation which is aimed at solving and solving problems through selected lifestyle activities. During the COVID 19 pandemic, cultivating Eco literation-based green behavior can be provided through online learning by utilizing digital technology through modeling, habituation, and repetition in everyday life such as consuming healthy food, exercising diligently, carrying out health protocols (diligently washing hands with soap and running water, wearing masks and keeping your distance), besides teaching people to limit activities that can harm themselves and the environment, which are packaged attractively and conveyed through various digital media such as blogs, websites, podcasts, and other social media